FRI0252 HIGH EARLY MORTALITY IN IDIOPATHIC INFLAMMATORY MYOPATHIES: RESULTS FROM INCEPTION COHORT AT A TERTIARY CARE CENTER IN NORTHERN INDIA. (2nd June 2020) - Mehta, P.; Gupta, L.
Abstract : Background: The idiopathic inflammatory myopathies (IIM) lead to significant morbidity and mortality. Understanding short term outcomes is the 1st step towards addressing risk factors for poor prognosis. Objectives: To assess the response to therapy, disease and treatment related morbidity and mortality in an inception cohort of IIM and determine the predictors of early mortality. Methods: Sixty-nine patients with a physician diagnosis of IIM as per 2017 ACR/EULAR classification criteria were recruited into an inception cohort from Dec 2017 to Nov 2019. Their follow-up data was recorded from June 2019 to December 2019. Clinical, laboratory and outcome variables were recorded as delineated in Figure 1A . Baseline characteristics were compared between deaths versus survivors, responders versus non-responders and those with and without major infections. Results are expressed as median (IQR). SPSS, v23, IBM 2010 was used for statistical analysis. Results: Of the 69 (54 female and 15 male) patients of median age 40 (23-51) and disease duration 3 (IQR 1-6) months, Dermatomyositis (DM) was the most common subset 26 (37.6%) (Fig, 1B ). Myositis Specific and Myositis Associated Antibody (MSA and MAA) were positive in 30 (43.4%) and 11 (17%) respectively (Fig. 1 C). Forty-eight patients followed-up over 10 (IQR 4.5-13) months accounting for 473 patient years, of which 8 (16.6%) suffered mortality and three PM were reclassified (Fig, 1B ). Four (10%) had minimal, 3 (7.5%) had moderate and 33 (82.5%) had a major clinical response (Fig. 2A ) with treatment. Eight (20%) of the 40 who survived had a relapse and 13 (32.5%) had steroid related complications. Eleven (27.5%) had at least 1 infection and it correlated with duration of steroid use (p-0.009, RR 0.78, 0.6-0.9) but not the cumulative dose of steroid (p-0.147) Duration of symptoms prior to treatment, subtype of myositis, MSA or presence of ILD did not predict the short-term response. 6-month survival was 83.3% (Figure 2B ). Rapidly progressive ILD was the most common cause of death followed closely by malignancy and infection (n=3, 37.5%)(Table 1 ). Diagnosis of Cancer associated myositis (OR 6.1), positive anti-MDA5 (OR 5.8) and a negative ANA (OR 5.8) were predictors of early mortality. Conclusion: Indian patients with IIM suffer high early mortality attributable to RP ILD, cancer and infections. Positive anti-MDA 5 and a negative ANA predict poor survival. Acknowledgments: Muscle Autoantibody testing was funded by APLAR. Disclosure of Interests: None declared